2018
DOI: 10.3390/molecules23082064
|View full text |Cite
|
Sign up to set email alerts
|

Gelatin as a Photosensitive Material

Abstract: Because this issue journal is dedicated to Gelatin, here we present a few applications of gelatin in the field of optics. Optics is the science that studies the production, propagation, interaction and detection of light. Various materials sensitive to light (photosensitive) are used for detection of light, such as photomultipliers, CCDs, crystals, two dimensional (2D) materials and more. Among the 2D materials, the most popular for several centuries has been gelatin based photographic emulsion, which records … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(32 citation statements)
references
References 113 publications
(123 reference statements)
0
30
0
2
Order By: Relevance
“…and pigment-lacking the more typical imaging metals, such as in silver halide photographic prints. Despite the vast history that gelatine has as a photosensitive material [19], we use it here only as a binder for the ink, as upon heating above ∼40°C it flows easily and can be stored as a 'frozen' solution in the fridge (∼6°C), where it sets to a gel. Additionally, it is fairly uniformly transparent in the visible region [20] and so provides less optical interaction with the pigment used.…”
Section: Experimental Methods-ink Formulation and Optical Measurementsmentioning
confidence: 99%
“…and pigment-lacking the more typical imaging metals, such as in silver halide photographic prints. Despite the vast history that gelatine has as a photosensitive material [19], we use it here only as a binder for the ink, as upon heating above ∼40°C it flows easily and can be stored as a 'frozen' solution in the fridge (∼6°C), where it sets to a gel. Additionally, it is fairly uniformly transparent in the visible region [20] and so provides less optical interaction with the pigment used.…”
Section: Experimental Methods-ink Formulation and Optical Measurementsmentioning
confidence: 99%
“…PVA with a hydrolysis degree between 85% and 89% dissolves easily in water at RT, while PVA with a high hydrolysis degree (98–99+%) is not water-soluble at RT and can dissolve at temperatures between 80 °C and 90 °C [ 35 ]. GEL is completely soluble in water, but only at temperatures above 35–40 °C [ 38 ]. At lower temperatures, GEL will swell, rapidly absorbing 5–10 times its weight in water [ 38 ].…”
Section: Methodsmentioning
confidence: 99%
“…For instance, thin gelatin film (e.g., 90 µm thickness) is transparent to visible light and shows only 10% transmission of the medium-infrared light (λ = 10.6 µm), while the mid-infrared spectrum can be effectively absorbed by a thicker film (e.g., 15 µm thickness), which can be used for surface-relief gratings. [200,[205][206][207] In recent years, gelatin has also been used as a triboelectric material for energy harvesting, sensing, and self-powered systems. [106,[208][209][210] For example, Chang et al [209] reported a TENG device consisting of gelatin, glycerol, and PTFE that remains stable even in an environment with high relative humidity (RH).…”
Section: Gelatinmentioning
confidence: 99%